Hockey : Challenging Canada's Game - Au-delà du sport national - Anderson, Jennifer (Archivist); Ellison, Jenny, 1977- (Book collections on Project MUSE., 2018)
"For Canadians, hockey is the game. Shared experiences and memories-lacing up for the first time, shinny on an outdoor rink, Sidney Crosby's historic goal, or the one scored by Maurice Richard-make hockey more than just a game. While the relationship between hockey and national identity has been studied, where does the game fit into our understanding of multiple, diverse Canadian identities today? This interdisciplinary book considers hockey, both as professional and amateur sport, and both in historical and contemporary context, in relation to larger themes in Canadian Studies, including gender, race/ethnicity, ability, sexuality, geography, and reflects upon all aspects of hockey in Canadian life: play, fandom, sports broadcasting, and community activism. This interdisciplinary scholarly collection is an extension of the "Hockey in Canada: More Than Just a Game" exhibition presented by the Canadian Museum of History"--